Global Economic Crisis and Vertical Specialization in Developing Countries - Pitigala, Nihal (World Bank, Washington, DC, 2012)
The world has witnessed an impressive increase in trade over the past four decades. World merchandise trade increased from US$217 billion in 1962 to US$22.8 trillion in 2006. While industrialized countries accounted for the vast majority of this growth, between 1985 and 2006, developing countries' total trade increased from US$1.1 trillion to US$8.4 trillion, growing at an average annual rate of 9.8 percent, outpacing the world trade growth of 8.7 percent over this period. As the current economic and financial crisis unfolds, the world is now witnessing a dramatic and unexpectedly rapid contraction of trade, far beyond what would be expected in a typical Keynesian-style contraction (Baldwin, 2009). Developing countries are expected to be adversely affected as the volume of world trade is expected to decline by more than 2 percent in 2009, the first such decline since 1982 (World Bank, 2009). The emergence of vertical specialization has allowed a large number of developing countries to exploit their comparative advantages at a much finer level of specialization in global production chains, enabling them to both boost their exports and diversify away from traditional, commodity-based exports.